The Influence of Entrepreneural Orientation on the Growth of Micro, Small and Medium Enterprises in Kenya - Katialem Ruto Isaac (Kabarak University, 2025)
Abstract Micro, Small, and Medium Enterprises (MSMEs) are pivotal to Kenya‘s economic development, contributing to employment creation, innovation, and GDP growth. However, many continue to face persistent growth constraints, stagnation, and high failure rates despite various government and institutional support mechanisms. Against this backdrop, this study investigates the influence of Entrepreneurial Orientation (EO) on the growth of MSMEs in Kenya. EO, conceptualized as a multidimensional construct comprising innovativeness, risk-taking, proactiveness, autonomy, and competitive aggressiveness, is recognized as a key driver of firm performance, yet empirical evidence in Sub-Saharan Africa remains mixed and context-dependent. Anchored on Schumpeterian Entrepreneurship Theory, the Risk-Taking Theory of Entrepreneurship, and the Theory of Competitive Advantage, the study adopts the multidimensional perspective of EO advanced by Lumpkin and Dess (1996). A sequential mixed-methods design integrating positivist and pragmatic paradigms was employed. Quantitative data were collected from 284 MSMEs, comprising manufacturing firms registered with the Kenya Association of Manufacturers (KAM) and innovation-driven start-ups supported by NACOSTI. This phase was followed by qualitative interviews with 15 purposively selected MSME owners or managers to provide contextual insights. Quantitative analysis, conducted using SPSS (Version 26), involved descriptive statistics, factor analysis, correlation, and multiple regression. The results revealed that proactiveness (r = 0.631), risk-taking (r = 0.529), and innovativeness (r = 0.452) were positively correlated with MSME growth, while autonomy (r = –0.576) was negatively associated, and competitive aggressiveness (r = 0.318) showed a weak positive correlation. Multiple regression analysis confirmed proactiveness (β = 0.380, p < .001), innovativeness (β = 0.246, p < .001), and competitive aggressiveness (β = 0.219, p < .001) as significant positive predictors of growth. Conversely, autonomy (β = –0.323, p < .001) had a significant negative effect, and risk-taking was positive but statistically insignificant. The model explained 60.2% of the variance in MSME growth (R² = 0.602). Qualitative findings supported these results, indicating that innovation and proactive market engagement are central to competitiveness, while excessive autonomy can lead to poor coordination and strategic drift. The study concludes that EO has a significant influence on MSME growth in Kenya, although the impact of its dimensions varies. Proactiveness and innovativeness are strong growth drivers, while autonomy may hinder performance if not strategically managed. It recommends that MSME managers strengthen innovation, calculated proactiveness, and structured autonomy. At the same time, policymakers enhance EO through innovation incentives, access to finance, and collaborative industry networks to promote sustainable enterprise growth.
Full text
Keywords: Entrepreneurial Orientation; Growth; Micro; Small; and Medium Enterprises